High-Resolution MR for Follow-Up of Intracranial Steno-Occlusive Disease Treated by Endovascular Treatment - Wang, Junjie; Zhang, Shun; Lu, Jun; Qi, Peng; Hu, Shen; Yang, Ximeng; Chen, Kunpeng; Wang, Daming (Frontiers in Neurology, 2021)
Background and Purpose: An endovascular recanalization is an alternative option for symptomatic intracranial atherosclerotic steno-occlusive disease (ICAD). Accurate non-invasive alternatives to digital subtraction angiography (DSA) for follow-up imaging after endovascular treatment are desirable. We aimed to evaluate the image quality and diagnostic performance of high-resolution magnetic imaging in follow-up using DSA as a reference. Materials and Methods: From January 2017 to June 2021, data from 35 patients with 40 intracranial steno-occlusive lesions who underwent endovascular recanalization and received high-resolution magnetic resonance (HR-MR) follow-up were retrospectively collected in our prospective database. Studies were evaluated for the quality of visualization of the vessel lumen, restenosis rate, and accuracy of high-resolution magnetic resonance (HR-MR) with DSA used as the reference standard. Intraclass correlation coefficient (ICC) analyses were performed to assess the agreement between the two different readers. Results: In total, 40 intracranial steno-occlusive lesions in 35 patients, with 34 lesions undergoing balloon angioplasty [including 16 drug-coated balloons (DCBs)] and 8 lesions undergoing stenting were enrolled. The median age was 63.6 years (IQR 58.5–70.0 years), and the mean imaging follow-up time was 9.5 months (IQR 4.8–12.5 months). The median degrees of preprocedural and residual stenosis were 85.0% (IQR 75.0–99.0%) and 32.8% (IQR 15.0–50.0%), respectively. Intracranial periprocedural complications occurred in 1 (3.6%) patient. In the case of a stainless-steel stent (n = 1), there was a signal drop at the level of the vessel, which did not allow evaluation of the vessel lumen. However, this was visible in the case of nitinol stents (n = 7) and angioplasty (n = 34). The overall restenosis rate was 25.8% (n = 9). The DCB subgroup showed a lower rate of restenosis than the percutaneous transluminal angioplasty (PTA) subgroup [5.3% (2/13) vs. 35.7% (5/14)]. Conclusion: High-resolution magnetic resonance may be a reliable non-invasive method for demonstrating the vessel lumen and diagnostic follow-up after endovascular recanalization for ICAD. Compared with MR angiography (MRA), HR-MR showed a higher inter-reader agreement and could provide more information after endovascular recanalization, such as enhancement of the vessel wall.